2004
DOI: 10.1523/jneurosci.1897-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Localizing P300 Generators in Visual Target and Distractor Processing: A Combined Event-Related Potential and Functional Magnetic Resonance Imaging Study

Abstract: Constraints from functional magnetic resonance imaging (fMRI) were used to identify the sources of the visual P300 event-related potential (ERP). Healthy subjects performed a visual three-stimulus oddball paradigm with a difficult discrimination task while fMRI and high-density ERP data were acquired in separate sessions. This paradigm allowed us to differentiate the P3b component of the P300, which has been implicated in the detection of rare events in general (target and distractor), from the P3a component, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

64
352
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(421 citation statements)
references
References 69 publications
64
352
2
3
Order By: Relevance
“…2), including right superior temporal gyrus and bilateral frontal lobe. This finding is in agreement with previous reports (Bledowski et al, 2004;Strobel et al, 2008;Volpe et al, 2007). Prior research has demonstrated that discrimination between standard and non-standard infrequent stimuli reflects frontal lobe activation, sensible to attentional allocation (Goldstein et al, 2002;Polich, 2007;Volpe et al, 2007).…”
Section: P3a and P3b Neural Generator Patternssupporting
confidence: 93%
See 1 more Smart Citation
“…2), including right superior temporal gyrus and bilateral frontal lobe. This finding is in agreement with previous reports (Bledowski et al, 2004;Strobel et al, 2008;Volpe et al, 2007). Prior research has demonstrated that discrimination between standard and non-standard infrequent stimuli reflects frontal lobe activation, sensible to attentional allocation (Goldstein et al, 2002;Polich, 2007;Volpe et al, 2007).…”
Section: P3a and P3b Neural Generator Patternssupporting
confidence: 93%
“…Symptoms were scored using the Positive and Negative Syndrome Scale (PANSS) (Kay et al, 1987). Socio-demographic and clinical characteristics for both groups are shown in Each EEG recording was off-line re-referenced to the common average (Bledowski et al, 2004) and digitally filtered using a [0.5 40] Hz finite impulse response filter. Then, a three-step artifact rejection method was applied.…”
Section: Subjectsmentioning
confidence: 99%
“…Moreover, the OB P300 responses of Figure 5 (c) show a clear P300 subcomponent (termed as the P3b) elicited by the target at the parietal channel Pz, with a significantly higher amplitude and shorter latency for the Easy task condition. This supports earlier works which show that increased task difficulty recruits more sensory and working memory functions, yields longer stimulus evaluation time, and results in amplitude reduction and longer peak latency for the P3b -this subcomponent represents the executive control function, focused attention (Bledowski et al, 2004;Polich, 2007). Increased task difficulty also appears to engage frontal attentional mechanisms more strongly, producing a large frontal/central P300 component (also termed the P3a subcomponent of the P300) when a distracting stimulus interrupts attentional control (Comerchero and Polich, 1998;Hagen et al, 2006).…”
Section: Erps and Performance Measuressupporting
confidence: 89%
“…As suggested above, variegated P300 data sets can be subsumed by inhibitory modulation in this fashion. Figure 9 illustrates fMRI activation from a three-stimulus oddball task using non-novel distracter stimuli and a difficult target/standard task (Bledowski et al, 2004b). The pattern of fMRI hemodynamic responses indicates that strong frontal lobe activation occurs for distracter stimulus processing, with minimal temporal/parietal activation observed.…”
Section: P300 As Inhibition: a Hypothesismentioning
confidence: 99%